Across the Board: Hiroshi Imahori. Issue 3 (7th January 2015) - Imahori, Hiroshi
Abstract In this series of articles the board members of ChemSusChem discuss recent research articles that they consider of exceptional quality and importance for sustainability. This entry features Prof. Hiroshi Imahori, who discusses a concept in which photosensitizers and binuclear catalysts, both based on ruthenium complexes, can be combined to efficiently oxidize water similar to the Photosystem II in plants.